Integrasi Kurikulum Pendidikan Vokasional dan Pendidikan Islam di Madrasah Aliyah Berbasis Pesantren - Abd. Muis; St. Rodliyah; Imam Syafi'i (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the planning, implementation, and evaluation of vocational curricula in pesantren-based madrasahs as an integrative strategy to produce graduates who are technically competent, spiritually religious, and adaptive to labor market demands. The research was conducted at MA Nurul Qarnain Sukowono Jember and MA Al-Fauzan Labruk Lumajang using a qualitative-descriptive approach through in-depth interviews, observation, and documentation. The findings show that curriculum planning is carried out participatively, involving various stakeholders and based on SWOT analysis, Islamic values of Ahlussunnah wal-Jama'ah, and synchronization with national regulations. In its implementation, the madrasahs apply a project-based learning approach that integrates practical skills and Islamic character education, resulting in a Ã¢â‚¬Å“character-based skillsÃ¢â‚¬Â model rooted in the pesantren tradition. Meanwhile, curriculum evaluation is conducted in a tiered and collaborative manner through a modified CIPP model incorporating reflective, spiritual, and social dimensions, where student outcomes are assessed not only academically but also through community and market recognition. This study offers a theoretical contribution by enriching the theories of Gordon, Oliva, and the CIPP evaluation model, and presents a novelty in the form of a contextual-religious vocational curriculum model based on the pesantren system, which is feasible for adoption in contemporary Islamic education. The findings indicate that systemic integration of skills education and Islamic values can serve as a foundation for transforming madrasah education into a competitive and locally rooted system.